Low population genetic differentiation in the Orchidaceae: Implications for the diversification of the family - Phillips, R.; Dixon, Kingsley; Peakall, R. (2012)
A leading hypothesis for the immense diversity of the Orchidaceae is that skewed mating success and small, disjunct populations lead to strong genetic drift and switches between adaptive peaks. This mechanism is only possible under conditions of low gene flow that lead to high genetic differentiation among populations. We tested whether orchids typically exhibit high levels of population genetic differentiation by conducting a meta-analysis to compare mean levels of population genetic differentiation (FST) between orchids and other diverse families and between rare and common orchids. Compared with other families, the Orchidaceae is typically characterized by relatively low genetic differentiation among populations (mean FST = 0.146) at allozyme loci. Rare terrestrial orchids showed higher population genetic differentiation than common orchids, although this value was still lower than the mean for most plant families. All lines of evidence suggest that orchids are typically characterized by low levels of population genetic differentiation, even in species with naturally disjunct populations. As such, we found no strong evidence that genetic drift in isolated populations has played a major role in the diversification of the Orchidaceae. Further research into the diversification of the family needs to unravel the relative roles of biotic and environmental selective pressures in the speciation of orchids.